Energy Metabolism in Servicemen with Emotional Burnout - Yanchuk, P.I.; Mykolaychuk, O.M.; Veselsky, S.P.; Pampukha, I.V.; Loza, V.M. (Fiziolohichnyĭ zhurnal, 2025)
Emotional burnout induces hidden or overt disorders in the field of mental health. The article presents the results of a study of the relationship between the level of emotional burnout and the state of energy metabolism, according to biochemical indicators of the adenylyl system, in servicemen of the Armed Forces of Ukraine. The study was carried out in two stages: first, a diagnosis of professional burnout was carried out, and then a control and experimental group of subjects was formed to analyze biochemical changes in their body. Using the standard Burnout Assessment Tool questionnaire, as well as interviewing servicemen, some of them were diagnosed with professional emotional burnout due to the presence of four basic symptoms: exhaustion, alienation, cognitive and emotional disorders, and two secondary symptoms: psychological and psychosomatic complaints. Important for the diagnosis of burnout in the military was their confirmation of the feeling of depletion of their own resources, fatigue, changes in behavior and a certain deterioration in physical health. Cognitive and emotional impairments, as well as psychological and psychosomatic complaints, showed little difference between women and men on the main criteria, with notable differences only in the indicators of exhaustion and alienation. Saliva sampling allowed the assessment of the concentration of adenosine triphosphate (ATP), adenosine diphosphate (ADP), adenosine monophosphate (AMP), and other components of the adenylyl system. A relationship was found between the components of burnout (exhaustion, depersonalization, cognitive and emotional disorders) and the level of metabolic changes in the adenylyl system. In military personnel with emotional burnout, there was a significant decrease in the level of energy metabolism, as evidenced by a decrease in the content of ATP in their body due to a decrease in the efficiency of phosphorylation processes. The increased content of ADP in them indicates an intensification of the process of ATP breakdown and a decrease in its level. Under these conditions, there was an increase in the content of AMP, which is necessary for ADP resynthesis. At the same time, the concentration of metabolites of the breakdown of the main components of the adenylyl system: adenosine, xanthine, hypoxanthine and uric acid increased, which indicates a decrease in their involvement in the process of resynthesis of key high-energy metabolites..